THE USE OF MACRO FUNCTION IN TENNESSE WILLIAMÃ¢â‚¬â„¢S DRAMA Ã¢â‚¬Å“A STREETCAR NAMED DESIREÃ¢â‚¬Â DISCOURSE ANALYSIS - Citra Buana Halil; Azzan Wafiq Agnurhasta (Universitas Khairun, 2023)
This article aims to know particular types of macro function and how its appear in the utterances on the drama. The writer uses purposive sampling technique to choose which sample were to be analyzed. The data were determined according to it needs and purpose of this research. The writer found some samples from this research. There are seventy samples which called hard sample. The result of this research is macro functions further divided into types but the writer only take five function namely: emotiveÃ‚Â (10), metalinguistic(13), directiveÃ‚Â (18), phaticÃ‚Â (6), and referentialÃ‚Â (2).Keywords: Macro Function, Drama, and DiscourseÃ‚Â Analysis